Perbandingan Senam Tai Chi dan Senam Diabetes Mellitus terhadap Penurunan Kadar Gula Darah pada Pasien Diabetes Mellitus Tipe II (Journal of Telenursing (JOTING), 2019)
This study aims to determine the comparison of Tai Chi and DM exercises to reduce blood sugar levels in type II DM patients at Menjalin Health Center. The research design used was a Quasi experiment with a pre and post test group design approach. The results of the study using the Wilcoxon test in the Tai Chi group obtained the value of p = 0.000